Recomposition of Labor Migration to the Mexican Northern Border - PEÑA MUÑOZ, Jesús Javier (Frontera Norte, 2018)
For decades, the northern Mexican border registered economic and demographic growth above national average. Today, these levels of growth were fueled in part by high rates of labor immigration. Nowadays, this region is experiencing historic lows of incoming labor migration. This lack of labor migration comes as a result of a recomposition in quantity and sociodemographic characteristics of labor migration. Using data from Emif Norte, we explore some on the main changes behind this recomposition. As an example, we present the situation in Ciudad Juarez.